2019
DOI: 10.1021/acsbiomaterials.9b01265
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Cochlear Implant-Based Electric-Acoustic Stimulation of Spiral Ganglion Neurons

Abstract: Cochlear implants are currently the most effective treatment for profound sensorineural hearing loss. However, their therapeutic effect is limited by the survival and proper physiological function of spiral ganglion neurons (SGNs), which are targeted by the cochlear implant. It is therefore critical to explore the mechanism behind the effect of electric-acoustic stimulation (EAS) on the targeted SGNs. In this work, a biocompatible cochlear implant/graphene EAS system was created by combining a cochlear implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Loss of HCs, primarily resulting from noise trauma, ototoxic drugs, infections, aging, and genetic mutations, with sequential degeneration of SGNs, ultimately leads to permanent SNHL [7][8][9][10][11][12][13][14][15]. The current preferred treatment of SNHL for patients with profound HC loss and mostly intact SGNs includes cochlear implants, which uses electrode arrays to substitute for mechanosensory HCs in generating electrical impulses to the auditory nerve [16]. In order to promote regeneration and guiding of neurites from residual auditory neurons, many potential guidance cues are under research, due to their influence on neurite outgrowth behavior and subsequent performance of cochlear implants [6,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of HCs, primarily resulting from noise trauma, ototoxic drugs, infections, aging, and genetic mutations, with sequential degeneration of SGNs, ultimately leads to permanent SNHL [7][8][9][10][11][12][13][14][15]. The current preferred treatment of SNHL for patients with profound HC loss and mostly intact SGNs includes cochlear implants, which uses electrode arrays to substitute for mechanosensory HCs in generating electrical impulses to the auditory nerve [16]. In order to promote regeneration and guiding of neurites from residual auditory neurons, many potential guidance cues are under research, due to their influence on neurite outgrowth behavior and subsequent performance of cochlear implants [6,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…RNA transcriptomic analysis has been wildly used in the hearing research fields to identify the differentially expressed genes [35][36][37][38][39][40][41]. Compared with previous studies that analyzed RNA transcriptomics, differential genes related to NIHL involve inflammation mediated by chemokines, cytokine pathways of the stress response, and immune pathways…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation generated by CI itself may also be one of the important factors to affect the survival of residual SGNs. Previous studies have reported that the electric conductive biomaterials and the electrical stimulation have very obvious effects on regulating the proliferation and differentiation of neural stem cells [ 44 , 45 ], as well as on regulating the survival and maturation of neurons, including SGNs [ 46 ]. In this study, we found that electrical stimulation could decrease the I Ca but had no effect on the action potential firing in cultured SGNs.…”
Section: Discussionmentioning
confidence: 99%